Multiphysics modeling using COMSOL5 and MATLAB - Pryor, Roger W. (Multiphysics modeling series, 2016)
"COMSOL 5 and MATLAB are valuable software modeling tools for engineers and scientists. This book explores a wide range of models in coordinate systems from 0D to 3D and introduces the numerical analysis techniques employed in COMSOL 5 (including Application Builder) and MATLAB software. The text presents electromagnetic, electronic, optical, thermal physics, and biomedical models as examples. It presents the fundamental concepts in the models and the step-by-step instructions needed to build each model. The book is designed to introduce modeling to an experienced engineer or can also be used for upper level undergraduate or graduate courses."--